Pengaruh Penerapan Good Corporate Governance Terhadap Kepatuhan Pajak Perusahaan Publik - , Urip Hudiarto; , Dr. Eko Suwardi, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this study is to examine the influence of implementation of Good Corporate Governance on Tax Compliance at public companies. The population of this study are public companies that listed on the Indonesia Stock Exchange. Sampling in this study using purposive sampling. The sample are public companies that have implemented good corporate governance and participate in the CGPI rating. Number of samples surveyed were 24 companies. The result of this study showed that the implementation of Good Corporate Governance Compliance enough to influence tax compliance at public companies. However, the influence of implementation of Good Corporate Governance on Tax Compliance only on Formal Tax Compliance. Implementation of Good Corporate Governance has no influence on Material Tax Compliance.